Iron Availability Influences Silicon Isotope Fractionation in Two Southern Ocean Diatoms (Proboscia inermis and Eucampia antarctica) and a Coastal Diatom (Thalassiosira pseudonana) - Meyerink, Scott; Ellwood, Michael J.; Maher, William A.; Strzepek, Robert (Frontiers in Marine Science, 2017)
The fractionation of silicon (Si) isotopes was measured in two Southern Ocean diatoms (Proboscia inermis and Eucampia Antarctica) and a coastal diatom (Thalassiosira pseudonana) that were grown under varying iron (Fe) concentrations. Varying Fe concentrations had no effect on the Si isotope enrichment factor (ε) in T. pseudonana, whilst E. antarctica and P. inermis exhibited significant variations in the value of ε between Fe-replete and Fe-limited conditions. Mean ε values in P. inermis and E. antarctica decreased from (± 1SD) -1.11 ± 0.15‰ and -1.42 ± 0.41‰ (respectively) under Fe-replete conditions, to -1.38 ± 0.27‰ and -1.57 ± 0.5‰ (respectively) under Fe-limiting conditions. These variations likely arise from adaptations in diatoms arising from the nutrient status of their environment. T. pseudonana is a coastal clone typically accustomed to low Si but high Fe conditions whereas E. antarctica and P. inermis are typically accustomed to High Si, High nitrate low Fe conditions. Growth induced variations in silicic acid (Si(OH)4) uptake arising from Fe-limitation is the likely mechanism leading to Si-isotope variability in E. antarctica and P. inermis. The multiplicative effects of species diversity and resource limitation (e.g. Fe) on Si-isotope fractionation in diatoms can potentially alter the Si-isotope composition of diatom opal in diatamaceous sediments and sea surface Si(OH)4. This work highlights the need for further in-vitro studies into intracellular mechanisms involved in Si(OH)4 uptake, and the associated pathways for Si-isotope fractionation in diatoms.